Research on the risk adjacency matrix based on attack graphs - YE Yun; XU Xi-shan; JIA Yan; QI Zhi-chang; CHENG Wen-cong (Tongxin xuebao)
Aimed at the problem that the difficulty to understand the very complicated attack graphs generated by a variety of existing tools,a method of RAM（risk adjacency matrix） based on attack graphs was proposed,and feasibility and efficient of proposed method was verified in experiment.The experimental results on the network showed that visualization of attack graphs was extended significantly,and the re-computing problem caused by the rings and loops in the risk assessment was solved in a simple and efficient way.